World Economic and Financial Surveys : International Capital Markets 1990. (World Economic and Financial Surveys; World Economic and Financial Surveys, 1990)
This paper presents the annual survey of international capital market developments and prospects. It reviews trends in the main market segments and seeks to analyze the principal forces underlying these developments, in particular the progressive integration of markets and the related globalization of investor and borrower behavior. Buoyant activity in international capital markets during 1988 and 1989 reflected a continued strong economic expansion in most industrial countries, a high level of investment activity, an increase in the volume of world trade, and an environment of relatively stable prices and exchange rates. The broad exchange market stability in this period, which reflected in part the resolve of the authorities of the Group of Seven (G-7) to stabilize exchange rates in the wake of the Plaza agreement, meant that nominal interest rate differentials had a greater influence than in 1987 on financial flows. The surge of activity on international bond markets in 1988 and 1989 was facilitated by the continued expansion of the swaps market, which allowed the portfolio preferences of borrowers and lenders to be more easily matched.